Inkonsistensi Kebijakan Luar Negeri Melanesia Spearhead Group (MSG) dalam Isu Papua Barat: Studi Kasus Fiji dan Papua Nugini - Muhammad Fadhilah (Universitas Diponegoro, 2019)
West Papua issue is one of the most dynamic issue, especially in South Pacific region. Melanesian Spearhead Group is one of the organization from Melanesia sub-region which very actively engaging in decolonization and human rights issue in West Papua. Since the establishment in 1988, the organization which consist of four Melanesian states plus one independence movement party have been supporting the decolonization issue in the region. However, MSG foreign policy in West Papua issue is characterized by inconsistency when dealing with the struggle to support the decolonization. Instead of expressing strong opposition toward Indonesia’s human rights abuses in West Papua, MSG tends to engage Indonesia. This paper aims to explain this puzzle using the case study of Fiji and Papua New Guinea. This paper emphasizes on domestic factors which affect two countries foreign policy in West Papua issue. Using the concept of national interest combined with domestic constraint on foreign policy as a tool of analysis, this paper argues that the inconsistency of two MSG member countries foreign policy is caused by domestic factors